Endogenous protein C has a protective role during Gram‐negative pneumosepsis (melioidosis). Issue 2 (7th February 2013) - Kager, L. M.; Wiersinga, W. J.; Roelofs, J. J.; Meijers, J. C. M.; Zeerleder, S. S.; Esmon, C. T.; van, C.; van der, T.
Summary Background Activated protein C (APC) exerts anticoagulant effects via inactivation of factors Va and VIIIa and cytoprotective effects via protease activated receptor (PAR)1. Inhibition of endogenous APC in endotoxemia and sepsis results in exacerbation of coagulation and inflammation, with consequent enhanced lethality. Objectives We here sought to dissect the distinct roles of the anticoagulant and cytoprotective functions of endogenous APC in severe Gram‐negative pneumonia‐derived sepsis (melioidosis). Methods We infected wild‐type (WT) mice with Burkholderia pseudomallei, a common sepsis pathogen in southeast Asia, and treated them with antibodies inhibiting both the anticoagulant and cytoprotective functions of APC (MPC1609) or the anticoagulant functions of APC (MAPC1591) only. Additionally, we administered SEW2871 (stimulating the S1P1‐pathway downstream from PAR1) to control and MPC1609‐treated mice. Results MPC1609, but not MAPC1591, significantly worsened survival, increased coagulation activation, facilitated bacterial growth and dissemination and enhanced the inflammatory response. The effects of MPC1609 could not be reversed by SEW2871, suggesting that S1P1 does not play a major role in this model. Conclusions These results suggest that the mere inhibition of the anticoagulant function of APC does not interfere with its protective role during Gram‐negative pneumosepsis, suggesting a more prominent role for cytoprotective effects of APC .